Original antigenic sin and apoptosis in the pathogenesis of dengue hemorrhagic fever. - Mongkolsapaya, J; Dejnirattisai, W; Xu, X; Vasanawathana, S; Tangthawornchaikul, N; Chairunsri, A; Sawasdivorn, S; Duangchinda, T; Dong, T; Rowland-Jones, S; Yenchitsomanus, P; McMichael, A; et al. (2003)
Dengue virus presents a growing threat to public health in the developing world. Four major serotypes of dengue virus have been characterized, and epidemiological evidence shows that dengue hemorrhagic fever (DHF), the more serious manifestation of the disease, occurs more frequently upon reinfection with a second serotype. We have studied dengue virus-specific T-cell responses in Thai children. During acute infection, few dengue-responsive CD8+ T cells were recovered; most of those present showed an activated phenotype and were undergoing programmed cell death. Many dengue-specific T cells were of low affinity for the infecting virus and showed higher affinity for other, probably previously encountered strains. Profound T-cell activation and death may contribute to the systemic disturbances leading to DHF, and original antigenic sin in the T-cell responses may suppress or delay viral elimination, leading to higher viral loads and increased immunopathology.